Integrasi Nilai Pancasila dalam Pelatihan Batik Ciprat untuk Meningkatkan Kemandirian Ekonomi Wanita Agen Pancasila - Prasetyo, Kuncoro Bayu; Maftukhatun Nashikhah; Novenda, Maya (Jurnal Bina Desa, 2025)
The empowerment of women agency Pancasila is one of the movements carried out to improve the quality of the role of women in society. Implementation of dedication UNNES GIAT 9 Village Gledeg in women empowerment involves values Pancasila carried out with training batik ciprat techniques. Batik ciprat was chosen as a media because it is one of the Indonesian cultural heritage that can be developed into an independent and creative economic enterprise. The integration of Pancasila's values into the training provides a foundation for strengthening the understanding and appreciation of the values of pancasila in everyday life. This dedication aims to enhance the glory and economic independence of women by collaborating on the values of Pancasila. These include skills improvement, motivation, and character strengthening based on Pancasila. The ciprat batik training provides new skills that the PKK mother of Village Gledeg possesses which have a high usage value and a high sales value. Besides, training in cyprus battery engineering also provides business opportunities to improve the economy of the community. The implementation of devotional activities through batik ciprat training is carried out in three stages namely preparation, execution, and, final. The training of the batik ciprates produces batik fabrics that can be used as valuable products such as clothes, bags, hats, and so on.